Consequences of changes in the educational field at the end of the 21st century. Customizations for history teaching - Boșcodeală, Felicia Elena (Technium Social Sciences Journal, 2022)
There are permanent approaches regarding the role and purpose of history in the context of the 3rd millennium. The idea that history should and can be studied was strongly emphasized because people need to know themselves. Three sources of fundamental knowledge of history were mentioned for the 20th and 21st centuries: school, family, mass media. Contemporary specialists warn that the success of teaching history in school should not be based on a strictly mechanical assimilation of historical data and events, but above all on the understanding by the subjects of history learning of the significance of historical processes, events and progress over time, but and to the contribution of history to the formation of national identity. This explains why the study of history is closely linked to education for democratic citizenship and human rights.